2020
DOI: 10.1111/jonm.13174
|View full text |Cite
|
Sign up to set email alerts
|

The association between workplace social capital and authentic leadership, structural empowerment and forms of communication as antecedent factors in hospital nurses: A cross‐sectional multilevel approach

Abstract: Aim To identify the effects of authentic leadership, structural empowerment and forms of communication as antecedent factors of workplace social capital in nursing. Background Enhancing workplace social capital for nurses by management requires identifying antecedent factors of workplace social capital focusing on work environment and relationships between members. Methods In 2019, self‐administered questionnaires were sent to all nurses working on the general wards of two university hospitals in Japan. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Also, this study suggests that some personal factors and characteristics of the work environment, such as nurses’ years of experience, number of COVID-19 patients, bed capacity, and patient-to-nurse ratio, may affect nurses’ leadership practices. The result supported the proposition of Kouzes and Posner’s leadership model ( Kouzes & Posner, 2003 ), and was also similar to studies that revealed that nurses’ who perceive a strong structural and psychological empowerment felt more independent and motivated in their work ( Chang & Liu, 2008 ) and demonstrated leadership behaviors ( Bish, Kenny, & Nay, 2015 ; Kida, Togari, Yumoto, & Ogata, 2021 ). These findings indicated that structural/psychological empowerment is key for nurses to develop and practice leadership activities.…”
Section: Discussionsupporting
confidence: 86%
“…Also, this study suggests that some personal factors and characteristics of the work environment, such as nurses’ years of experience, number of COVID-19 patients, bed capacity, and patient-to-nurse ratio, may affect nurses’ leadership practices. The result supported the proposition of Kouzes and Posner’s leadership model ( Kouzes & Posner, 2003 ), and was also similar to studies that revealed that nurses’ who perceive a strong structural and psychological empowerment felt more independent and motivated in their work ( Chang & Liu, 2008 ) and demonstrated leadership behaviors ( Bish, Kenny, & Nay, 2015 ; Kida, Togari, Yumoto, & Ogata, 2021 ). These findings indicated that structural/psychological empowerment is key for nurses to develop and practice leadership activities.…”
Section: Discussionsupporting
confidence: 86%
“…Workplace social capital is an intangible but a formidable source that can improve effectivity and productivity of a workforce ( 3 ). Nurses' workplace social capital, a derivative of the concept of workplace social capital, has promising impacts beyond nursing professionals ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This leadership style acknowledges the importance of ethical standards, transparency, honesty, authenticity and integrity in cultivating a quality leader–subordinate relationship (Avolio & Gardner, 2005; Gardner et al, 2011), resulting in increased work commitment and job engagement and sustained job performance in their subordinates (Avolio, 2004). Considerable evidence exists in the realm of nursing linking authentic leadership of nurse leaders with enhanced nurses' work outcomes (Kida et al., 2020; Maziero et al., 2020; Regan et al., 2016) and heightened psychological well‐being (Wei et al., 2020; Alilyyani et al., 2018; Shirey et al, 2019). However, there are limited yet valuable reports that relate authentic leadership to patient safety outcomes including fewer adverse events (Asif et al., 2019; Wong et al., 2013) and improved care quality (Puni & Hilton, 2020; Laschinger & Fida, 2015).…”
Section: Introductionmentioning
confidence: 99%